Chylothorax after myocardial revascularization with the left internal thoracic artery - Pêgo-Fernandes,Paulo Manuel (1999)
A 38-year-old male underwent coronary artery bypass grafting (CABG). A saphenous vein graft was attached to the left marginal branch. The left internal thoracic artery was anastomosed to the left anterior descending artery (LAD). The early recovery was uneventful and the patient was discharged on the 5th postoperative day. After three months, he came back to the hospital complaining of weight loss, weakness, and dyspnea on mild exertion. Chest X-rays showed left pleural effusion. On physical examination, a decreased vesicular murmur was detected. After six days, the diagnosis of chylothorax was made after a milky fluid was detected in the plural cavity and total pulmonary expansion did not occur. On the next day, both anterior and posterior pleural drainage were performed by videothoracoscopy, and prolonged parenteral nutrition (PPN) was instituted for ten days. After seven days the patient was put on a low-fat diet for 8 days. The fluid accumulation ceased, the drains were removed and the patient was discharged with normal pulmonary expansion.